Influence of Egr-1 in Cardiac Tissue-Derived Mesenchymal Stem Cells in Response to Glucose Variations. (22nd May 2014) - Bastianelli, Daniela; Siciliano, Camilla; Puca, Rosa; Coccia, Andrea; Murdoch, Colin; Bordin, Antonella; Mangino, Giorgio; Pompilio, Giulio; Calogero, Antonella; De Falco, Elena
Abstract : Mesenchymal stem cells (MSCs) represent a promising cell population for cell therapy and regenerative medicine applications. However, how variations in glucose are perceived by MSC pool is still unclear. Since, glucose metabolism is cell type and tissue dependent, this must be considered when MSCs are derived from alternative sources such as the heart. The zinc finger transcription factor Egr-1 is an important early response gene, likely to play a key role in the glucose-induced response. Our aim was to investigate how short-term changes in in vitro glucose concentrations affect multipotent cardiac tissue-derived MSCs (cMSCs) in a mouse model of Egr-1 KO (Egr-1 −/− ). Results showed that loss of Egr-1 does not significantly influence cMSC proliferation. In contrast, responses to glucose variations were observed in wt but not in Egr-1 −/− cMSCs by clonogenic assay. Phenotype analysis by RT-PCR showed that cMSCs Egr-1 −/− lost the ability to regulate the glucose transporters GLUT-1 and GLUT-4 and, as expected, the Egr-1 target genes VEGF, TGF β -1, and p300. Acetylated protein levels of H3 histone were impaired in Egr-1 −/− compared to wt cMSCs. We propose that Egr-1 acts as immediate glucose biological sensor in cMSCs after a short period of stimuli, likely inducing epigenetic modifications.